The perspective of ceRNA regulation of circadian rhythm on choroidal neovascularization - Ying Yang; Shu Su; Jia Chen; Xiaowei Yang; Shenglai Zhang; Aimin Sang (Scientific Reports)
Abstract Abnormal growth of blood vessels (choroidal neovascularization) can lead to age-related macular degeneration (AMD) and eventually cause vision loss due to detachment of the retinal pigmented epithelium. This indicates that choroidal neovascularization is important for the treatment of AMD. The circadian clock in the mammalian retina is responsible for controlling various functions of the retina, enabling it to adjust to changes in light and darkness. Recent studies have revealed a potential connection between the circadian clock and eye diseases, although a cause-and-effect relationship has not been definitively established. C57BL/6J male mice (aged 6 weeks) were randomly divided into two groups (Control group: 9:00–21:00 light period (300 lx); Jet lag group: 8-hour phase advance once every 4 days). A laser-induced CNV model was created after 2 weeks of feeding in a controlled or jet-lagged environment. Then, full transcriptome sequencing was performed. The pathways regulated by differentially expressed mRNAs were identified by GO analysis and GSEA. Further protein networks were constructed with the STRING database and Cytoscape software. WGCNA was used to further explore the co-expression modules of these differential genes and the correlation between these differential genes and phenotypes. ceRNA networks were constructed with miRanda and TargetScan. The pathways associated with the overlapping differentially expressed mRNAs in the ceRNA network were identified, and the hub genes were validated by qPCR. A total of 661 important DEGs, 31 differentially expressed miRNAs, 106 differentially expressed lncRNAs and 87 differentially expressed circRNAs were identified. GO and GSEA showed that the upregulated DEGs were mainly involved in reproductive structure development and reproductive system development. The STRING database and Cytoscape were used to determine the protein interaction relationships of these DEGs. WGCNA divided the expression of these genes into several modules and screened the hub genes of each module separately. Furthermore, a ceRNA network was constructed. GO analysis and GSEA showed that these target DEmRNAs mainly function in wound healing, cell spreading, epiboly involved in wound healing, epiboly, and morphogenesis of an epithelial sheet. Finally, ten key genes were identified, and their expression patterns were confirmed by real-time qPCR. In this study, we investigated the regulatory mechanism of ceRNAs in choroidal neovascularization according to different light-dark cycles in the eyeball.